2022
DOI: 10.1021/acs.jafc.1c07927
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Contributes to Copper-Induced Pyroptosis via Regulating the IRE1α-XBP1 Pathway in Pig Jejunal Epithelial Cells

Abstract: Copper (Cu) is a common additive in food products, which poses a potential concern to animal and human health when it is in excess. Here, we investigated the relationship between endoplasmic reticulum (ER) stress and pyroptosis in Cu-induced toxicity of jejunum in vivo and in vitro. In in vivo experiments, excess intake of dietary Cu caused ER cavity expansion, elevated fluorescence signals of GRP78 and Caspase-1, and increased the mRNA and protein expression levels related to ER stress and pyroptosis in pig j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Our previous findings demonstrated that the copper contents was found to be significant accumulated in hindgut digesta with increased dietary copper levels in rats and piglets, the accumulation of copper alters the composition of intestinal microbiota in both animals 8 , 15 . More importantly, a significant correlation between the alterations of intestinal microbiota and serum TNF-α concentration was observed in rat experiments, which suggested that TNF-α could be the chief responder to microbiota shift under excessive copper exposure 1 . Otherwise, the correlation analysis of microbiome-metabolome suggested that dietary high-level copper alter the composition of the gut microbiota and modulate microbial metabolic pathways, which may further affect the health of suckling piglets 2 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our previous findings demonstrated that the copper contents was found to be significant accumulated in hindgut digesta with increased dietary copper levels in rats and piglets, the accumulation of copper alters the composition of intestinal microbiota in both animals 8 , 15 . More importantly, a significant correlation between the alterations of intestinal microbiota and serum TNF-α concentration was observed in rat experiments, which suggested that TNF-α could be the chief responder to microbiota shift under excessive copper exposure 1 . Otherwise, the correlation analysis of microbiome-metabolome suggested that dietary high-level copper alter the composition of the gut microbiota and modulate microbial metabolic pathways, which may further affect the health of suckling piglets 2 .…”
Section: Introductionmentioning
confidence: 88%
“…Significantly changed Na, K, Mg, Mn and Cu concentrations in hair can reflect the adverse effects of dietary 300 mg•kg −1 copper of suckling piglets. We believe our results may benefit people to gain a better understanding of the ion interactions and metabolic homeostasis of heavy metal elements that are critical to human and animal health.Copper is a crucial trace element for the normal and healthy growth of mammals [1][2][3][4][5] . It has been found that at higher concentrations, copper exposure has been linked to liver disease, neurological disorders, reproductive abnormalities, and a multitude of other detrimental impacts on humans and animals 3,6 .…”
mentioning
confidence: 99%
“…Another study reported that excessive intake of Cu 2+ can cause ER expansion, increase the expression of GRP78 and caspase1 proteins, and increase the expression of ERS and pyroptosis-related proteins and mRNAs, indicating that Cu 2+ can cause pyroptosis through ERS. In addition, they found that both 4-Phenylbutyric acid (4-PBA, ERS inhibitor) and MKC-394 (IRE1α inhibitor) could inhibit ERS to alleviate the occurrence of pyroptosis [ 55 ]. These results suggest that ERS regulates copper ion-induced pyroptosis through the IRE1α-XBP1 pathway (Fig.…”
Section: Cell Death Mediated By Ers and Uprmentioning
confidence: 99%
“…Excess Cu induced pyroptosis by generating ROS in hepatocytes, and the inhibition of Caspase-1-dependent pyroptosis might attenuate Cu-induced apoptosis [ 155 ]. In addition, there are research findings that ER stress also participated in regulating Cu-induced pyroptosis in jejunal epithelial cells via the IRE1 α -XBP1 pathway [ 156 ], which provided a novel view into the toxicology of copper.…”
Section: Defective Copper Metabolism and Dcmmentioning
confidence: 99%